Association Between Whole-Body Vibration and Low-Back Disorders in Farmers: A Scoping Review. Issue 1 (2nd January 2018) - Kwaku Essien, Samuel; Trask, Catherine; Khan, Muhammad; Boden, Catherine; Bath, Brenna
ABSTRACT: Introduction: Low-back disorders (LBDs) are the most common musculoskeletal problem among farmers, with higher prevalence rates than in other occupations. Farmers who operate tractors and other types of machinery can have substantial exposure to whole-body vibration (WBV). Although there appears to be an association between LBDs and WBV, the causal relationship is not clear. Objective: This scoping review investigates the association between WBV and LBDs specifically among farmers. Methods: Nine databases were searched using groups of terms for two concepts: 'farming' and 'low back disorder'. Screening, data extraction, and quality assessment were performed by two reviewers independently. Included studies met the following criteria: focused on adult farmers/agricultural workers; assessed exposure to operating farm machinery such tractor, combine, or all-terrain vehicle; assessed LBDs as an outcome; and reported an inferential test to assess the relationship between WBV and LBD. Results: After 276 full texts screened, 11 articles were found to analyze WBV as a risk factor for LBDs. Three were case–control, five cross-sectional, and three retrospective cohorts. Four studies showed no association between WBV and LBDs, four a positive association, and three results were mixed depending on the exposure/outcome measure. Conclusion: A firm conclusion is difficult due to heterogeneity in, LBDs definition, type of farm commodity, study design, and statistical strategy. Direct comparisons and synthesis were not possible. Although retrospective cohort studies tended to show a relationship, future studies with a prospective cohort design could help clarify this association further.